Nigam’s inverted curtain hernioplasty: a modified lichtenstein tension free hernioplasty for inguinal hernia - Nigam, Vinod Kumar; Nigam, Siddharth (International Surgery Journal, 2019)
Background: It is an open tension-free hernioplasty for primary inguinal hernias using minimal dissection and only 3 sutures to fix the mesh. Methods: A description of operative technique and patient’s demographics are presented. Results: 362 repairs were done with this technique over a period 18 years (March 2000 to March 2018). All were primary uncomplicated inguinal hernias. Conclusions: NICH tackles the both known aetiological factors for recurrence i.e., weakness in inguinal floor and tension at the suture line. It involves minimal tissue dissection and least number of sutures. Two sutures are used to fix the mesh with inguinal ligament. Third suture is used to make an artificial deep inguinal ring in the mesh as well as used to narrow the natural deep inguinal ring to further avoid recurrence. No suture is applied in main body of mesh which remains free like an inverted curtain covering the whole hernia susceptible region of groin. Prolene mesh is used which completely covers the potentially weak area on the floor of inguinal region irrespective of the size of the area in small or big frame persons. Semi double breasting of external oblique aponeurosis avoids displacement of mesh. NICH is associated with least recurrence, less post-operative pain, less post-operative complications and short learning curve.